Can't finish what you started? The effect of climactic interruption on behavior - Kupor, Daniella M.; Reich, Taly; Shiv, Baba (Journal of Consumer Psychology, 2015)
AbstractIndividuals experience a greater frequency of interruptions than ever before. Interruptions by e‐mails, phone calls, text messages and other sources of disruption are ubiquitous. We examine the important unanswered question of whether interruptions can increase the likelihood that individuals will choose closure‐associated behaviors. Specifically, we explore the possibility that interruptions that occur during the climactic moments of a task or activity can produce a heightened need for psychological closure. When an interruption prevents individuals from achieving closure in the interrupted domain, we show that the resulting unsatisfied need for psychological closure can cause individuals to seek closure in totally unrelated domains. These findings have important implications for understanding how consumer decisions may be influenced by the dynamic—and often interrupted—course of daily events.